Kadar N-Terminal Pro-Brain Natriuretic Peptide sebagai Prediktor Luaran Klinis Sindrom Koroner Akut - Tandhana, Florencia Idajanti; Noormartany, Noormartany; Aprami, Toni M.; Tristina, Nina (Majalah Kedokteran Bandung, 2012)
Kadar N-terminal pro-brain natriuretic peptide (NT-proBNP) plasma dapat menggambarkan tingkat keparahan iskemia walaupun tidak terjadi nekrosis, iskemia yang transien dapat meningkatkan peregangan dinding jantung yang akan menginduksi sintesis dan pelepasan brain natriuretic peptide (BNP) yang sebanding dengan tingkat keparahan iskemia. Tujuan penelitian untuk mengetahui apakah kadar NT-proBNP pada penderita sindrom koroner akut (SKA) dapat digunakan sebagai parameter prediktor luaran klinis. Penelitian dilakukan sejak bulan Januari hingga Maret 2010. Subjek penelitian penderita SKA yang datang ke Unit Gawat Darurat Rumah Sakit Dr. Hasan Sadikin Bandung dan telah didiagnosis klinis sesuai kriteria World Health Organization. Pada subjek yang memenuhi kriteria inklusi dilakukan pemeriksaan kadar NT-pro BNP dengan metode electrochemiluminescence immunoassay, cardiac troponin T (kuantitatif), dan creatine kinase muscle brain (enzimatik). Analisis data uji normalitas menggunakan one-sample Kolmogorov-Smirnov test, analisis regresi logistik multipel untuk mengetahui parameter prediktor luaran klinis penderita SKA. Dari 83 subjek yang ikut dalam penelitian, didapatkan nilai prediksi kadar NT-proBNP sebesar 1,00 sehingga bukan merupakan prediktor utama luaran klinis, koefisien β NTproBNP sebesar 0,001 menyatakan bahwa setiap penambahan 1.000 pg/mL variabel NT-proBNP akan menambah lama perawatan 1 hari. Pada subjek SKA dengan luaran (outcome) sembuh nilai prediksi cTnT lebih baik sebagai faktor prediktor dibandingkan dengan konsentrasi NT-proBNP (OR=32,53; 95%IK; 0,58–1.819,26). Simpulan, NT-proBNP bukan merupakan prediktor utama luaran klinis pada SKA. Kadar NT-proBNP lebih dari 826,7 pg/mLterdapat kemungkinan prognosis yang buruk sampai dengan kematian. [MKB. 2012;44(2):106–13].The Role of NT-proBNP as Clinical Outcome Predictor for Acute Coronary SyndromesPlasma levels of N-terminal pro-brain natriuretic peptide (NT-proBNP) levels may reflect the severity of ischemia, although there is no necrosis. A transient ischemia which can increase the heart wall stretch would induces BNP synthesis and release. Synthesis and release of BNP are comparable with the severity of ischemia. The aim of this study was to analyze whether NT-proBNP levels in patients with acute coronary syndrome (ACS) can be used as a predictor for clinical outcome. Studies was held since January to March 2010. Subject were patients with ACS who came to emergency room Dr. Hasan Sadikin Hospital Bandung and were clinically diagnosed according to World Health Organization criteria. Subjects which were suited with the inclusion criteria, stored until assayed. NT-pro BNP concentration was examined by electrochemiluminescence immunoassay method along with creatine kinase muscle brain (enzymatic method) and cardiac troponin T (quantitative method). Statistical analysis was performed using the one-sample Kolmogorov-Smirnov test for verifying normality, normally distributed data were analyzed using parametric analysis and abnormal distributed data was assayed using multiple logistic regression analysis to determine the parameters which can be used as predictor for clinical outcome in patients with ACS. Multiple logistic regression analysis on 83 subjects showed predictive value of NT-proBNP levels with OR=1.00, which mean there was no different likelihood in patients with high and low concentration of NT-proBNP to have longer hospitality duration. NT-proBNP β coefficient of 0.001 states that every addition of 1,000 pg/mL of NT-proBNP concentration will increase the length of hospitality duration for one day. On convalesce subjects, the most significant predictive value for predicting clinical outcome cTnT was more better than NT-proBNP concentration in patients with ACS (OR=32.53, 95%CI; 0.58–1,819.26). In conclusions, NT-proBNP is not a major predictor of clinical outome in ACS. NT-proBNP levels of >826.7 pg/mL implies a poor prognosis to death. [MKB. 2012;44(2):106–13]. DOI: http://dx.doi.org/10.15395/mkb.v44n2.132